Os róticos em posição de coda: uma análise variacionista e acústica do falar piauiense - Carvalho, Lucirene da Silva (2009)
This thesis will examine the phonetic-phonological behaviour of rhotic in position of coda in the speech of 36 subjects from the north of Piauí state and the capital- Teresina. For this study, the sociolinguistic approach was used, with the support of the Variation Theory. In the findings four variants were found, the glottal fricatives [h] with 48.1% and zero phonetic [ø] with 22.2%, those which obtained the highest percentage of occurrence with 48.1% of occurences. On the other hand, the tap [] showed 19.01% and the palatal fricative [] with 10.6% of realization. Taking into consideration the more recurring variants, the findings show that the search results revealed that these variations are due to both the linguistic and social limitations, but they are more sensitive to the phonetic-phonological context. For the linguistic analysis, the previous and the following phonological context restrictions were considered, the position in syllable, the tone, the length of word and the grammatical category, were also taken into account, while for the social aspects, education, gender and age were chosen by the program Goldvarb. The findings showed that the restriction of the grammatical category was the one which most favored the variants, and the glottal fricative variants presented more evident results. From the acoustic view, with the help of the Acoustic Theory of Speech Production, in view of Kent and Read (1992), and other theoretitions linked to the acoustics perspective, in order to undertake an acoustic analysis of the segments /h/, /h/ e /h/, with emphasis on the latter two, considered in this study variations of [h]. To make such an analysis the study was grounded on the support of the Praat program. The results which were obtained from both linguistic analysis as well as acoustics analysis lead to the discussions concerning the behavior of the rhotic in Piauiense speech, noting that the four variants are recurrent in this speech community. However, the greatest focus was on the palatal fricative variant [], a realization not yet found in the pertinent linguistic literature. This phonetic-phonological phenomenon always happens before a silent glottal fricative when followed by a palatal fricative, also silent, and can be interpreted in two ways: first described as [h], which proves that the silent alveolar occlusive [t] constitutes the first consonant of silent affricate alveopalatal that blends with the following consonant. In this manner there is a kind of ressilabification of the merging type while maintaining the standard syllabic pattern CVC. CV remains the most simplified type. In the second realization one observes that the silent alveolar occlusive stays the same along with the affricate in the following syllabic attack. In both events evidence a kind of regressive assimilation was observed especially in the last occurrence, in which the assimilator is found after the assimmilated element. In both phenomena a partial type of palatalization was observed. This type of palatalization is a linguistic peculiarity restricted to specific language spoken in Piaui.